Tampilan Sifat Berbagai Galur F4Kedelai (Glycinemax [L.] Merrill)Hasil Persilangan Grobogan dengan KM14 dan KM25 - Sonya Litha H; Aslim Rasyad (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
The purpose of this research was to looked at genotypic performance,genetic variance and heritability of the traits associated with the yield components in several F4 soybean lines selected from crossing between Grobogan x KM14 and KM25. Materials used in this study were 23 genotypes consisting of 20 lines originated after selecting individual plant atthe F3 generation and three parental lines as control varieties. Each line was grown in the experimental station of Agriculture Faculty, Riau University. The field experiment was arranged in a randomized block design with three replications. The parameters observed were plant height, number of branches, flowering date, time to harvest, number of pods per plant, number of filled pods per plant, number of seeds per plant, number of seeds per pod, seeds weight per plant, seed yield per m2, 100-seed weight and harvest index. Data wereanalysed by the analysis of variance using the SAS version 9.03 program and followed by the Dunnet test at the 5% level. The results showed that there were genotypic differences between several lines and their parents for the character of plant height, number of pods per plant, number of filled pods, number of seeds per plant, weight of seeds per plant, number of seeds per pod, age of harvest, and yield per m2. Genetic component of variance was significant for plant height, number of filled pods, number of seeds per plant, weight of seeds per plant, harvesting date, and yield per m2.There were found that 9 F4 lines performed better than the three parents including GK-14-3-22, GK14-3-28, GK14-3-31, GK14-3-36, GK14-3-37, GK25-3-19, GK-25-3-27, GK-25-3-44 dan GK 25-3-36 having greater number of filled pods, number of seeds per plant and grain yield. Keywords:Soybean, Genotypic Performance, Heritability